Expert Consensus on the Clinical Application of Thymosin Alpha 1 in Infectious Diseases and Critical Care Medicine (Infectious Microbes & Diseases)
Abstract. As immunotherapy gains increasing attention and clinical application, the immune modulation therapy has been widely used in the treatment of infectious and critical diseases. Clinical evidence has been accumulated for application of thymosin alpha 1 (Tα1), a classical immune modulator, in related domains. The National Clinical Research Center for Infectious Diseases, National Medical Center for Infectious Diseases and other institutions invited multidisciplinary experts to develop this expert consensus on clinical application of Tα1 in infectious diseases and critical care medicine. Based on the latest domestic and international research findings and considering relevant factors, including economics, patient preferences and values, tradeoffs, accessibility, fairness and acceptability, the consensus assesses the quality levels of current evidence and forms 10 recommendations on the application of Tα1 in treatment of liver diseases, viral infections, bacterial infections and critical illnesses. This consensus aims to enhance understanding of Tα1 and improving its standardized application for clinicians.